Moringa Oleifera: Effective in Supporting Breastfeeding - KIREN KHURSHID MALIK MARIAM MALIK, MAHWISH NAJAM (Journal of Fatima Jinnah Medical University, 2018)
Objective: To study the effectiveness of Moringa Oleifera (Hilacta) in increasing milk production and thereby supporting breastfeeding. Study design: Randomized controlled double blind trial. Place and duration of study: The Department of Obstetrics and Gynaecology, Unit II, Sir Ganga Ram Hospital, Lahore from July 2010 to October 2010. Patients and methods: One hundred mothers in the Department of Obstetrics and Gynaecology Unit II, who had complaint of inadequate milk production in postnatal period, were included in this study. Participants were divided into two groups. Group A and Group B with fifty participants in each group. Group A was given A1 drug and Group B was given B2 drug. Dose of both drugs was two capsules twice a day for four weeks. Nature of product in both drug A1 and drug B2 was not known to the participants and researchers. Both drugs were identical in appearance and were in same packing. At regular follow-up visits results of both groups were collected and compared. Results: In Group B participants, establishment of lactation was early as compared to Group A participants. Also in Group B mothers were more satisfied when compared to Group A. Conclusion: Group B drug i.e. Moringa Oleifera (Hilacta) is effective in establishing and supporting breast feeding.